The Effect of a Land Titling Programme on Households’ Access to Credit - Piza, Caio; Barros de Moura, Mauricio José Serpa (Taylor and Francis, 2015)
This paper assesses the effects of property titling on households’ access to and use of credit by focusing on household responses to an exogenous change in their formal ownership status. We isolate the credit effect on legal ownership by comparing households from communities in Osasco, Brazil. Our statistical estimates suggest that land titling increases credit use, decreases reliance on credit borrowed from relatives, and increases credit borrowed from commercial banks. We also find that treated households increased their consumption of time-saving durable goods, which explains an observed reallocation of time among household members, with adults working more and children less.